Interobserver agreement and accuracy of non‐invasive diagnosis of endometriosis by transvaginal sonography. (2nd December 2015) - Tammaa, A.; Fritzer, N.; Lozano, P.; Krell, A.; Salzer, H.; Salama, M.; Hudelist, G.
ABSTRACT: Objectives: To evaluate interobserver agreement and accuracy of transvaginal sonography (TVS) in diagnosing deep infiltrating endometriosis (DIE) and endometriomas. Methods: A total of 67 consecutive patients referred to a pelvic pain clinic and scheduled for laparoscopy were enrolled in the study between January 2013 and January 2014. Patients were independently examined prospectively by two experienced sonographers (Observers A and B) who were blinded to the other's results. For the two observers, Gwet's first‐order agreement coefficient (Gwet's AC1) was used to calculate interobserver agreement and diagnostic accuracy, as well as sensitivity, specificity, positive (PPV) and negative (NPV) predictive values using TVS, as compared to laparoscopy, for diagnosing DIE and endometriomas. Results: Among the 67 patients enrolled, 65 were analyzed. For the diagnosis of DIE and endometriomas by TVS, the level of agreement (Gwet's AC1) between Observers A and B and sensitivity/specificity values for the respective Observers were, by site: vagina (Gwet's AC1, 0.933; 62%/94% and 82%/94%), bladder (Gwet's AC1, 1.00; 67%/97% and 67%/97%), uterosacral ligaments (Gwet's AC1, 0.84; 73%/83% and 53%/90%), adnexa (Gwet's AC1, 0.95; 71%/93% and 71%/93%), rectovaginal septum (Gwet's AC1, 0.95; 40%/90% and 33%/87%) and rectosigmoid (Gwet's AC1, 0.98; 93%/96% and 94%/98%) which reflected high interobserver agreement. With the exception of sensitivity of diagnosis of DIE affecting the RVS, similar results were observed when TVS was compared with laparoscopy. Conclusions: TVS is a highly accurate and reproducible method for non‐invasive diagnosis of DIE by well‐trained professionals. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.